TEACHING VOCABULARY BY USING PAVE STRATEGY TO THE THIRD GRADE STUDENTS OF SDN 182 PALEMBANG - Endang Susilo (Edukasi, 2015)
The objective of this study is to find out whether there is a significant difference on students’ achievement taught by using PAVE strategy and who were not. The writer use one of the quasi experimental designs, that is pretest posttest nonequivalent control group design to conduct this research. The population was all the third grade students of SD Negeri 182 Palembang in academic year 2012/2013 with total number 100 students. The sample of the study was 60 students taken by using convenience method. The writer used a test to collect the data. The writer used independent sample t-test to analyze the data. The result of the study showed that there was a significant difference on students’ vocabulary achievement taught PAVE strategy and those who were not. The value of t-obtained was 3.714. At a significant level 0.05 for the two tailed testing with degree of freedom (df) 58 the table was 2.021, t-test   showed that t-obtained higher than t-table as a critical value, the null hypothesis (Ho) in posttest was rejected and the research hypothesis (Ha) in pretest group was accepted. It means that there was significant difference posttest on students’ vocabulary achievement taught PAVE strategy of SD Negeri 182 Palembang. This research might be useful for teachers because it can help students, remember new words and it is more stimulating in teaching and larning process.